2017
DOI: 10.1177/1687814017725246
|View full text |Cite
|
Sign up to set email alerts
|

A review of essential technologies for collision avoidance assistance systems

Abstract: Compared with automatic collision avoidance systems, collision avoidance assistance systems have attracted more research interest because they help avoid collisions in near-accident situations. However, ensuring the robustness and reliability of collision avoidance assistances is difficult because of problems in reliable environment recognition, accurate collision avoidance decision making, and driver acceptance. This article reviews and analyzes three essential technologies for collision avoidance assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Finally, the simulation results showed that the intelligent right-turning vehicle collision probability calculation algorithm could calculate collision probability and the two- Scenario 2: when the vehicle turned right into the lane, it was difficult to find pedestrians who were crossing the road in the lane, so it was easy to cause serious traffic accidents. e parameters in this scenario were defined as follows: pt � 0.01 s, T � 5 s, L 1 � 8 m, W 1 � 2 m, and D � 1.5 m; the pedestrian's coordinates were (8,12). V 1 , V 2 , and R consist of 10,000 normally distributed random numbers, N (1, 2), and R ∼ N (20, 1); V 2 represented the velocity of the pedestrian in this case.…”
Section: Simulation Results Analysis Of Four Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the simulation results showed that the intelligent right-turning vehicle collision probability calculation algorithm could calculate collision probability and the two- Scenario 2: when the vehicle turned right into the lane, it was difficult to find pedestrians who were crossing the road in the lane, so it was easy to cause serious traffic accidents. e parameters in this scenario were defined as follows: pt � 0.01 s, T � 5 s, L 1 � 8 m, W 1 � 2 m, and D � 1.5 m; the pedestrian's coordinates were (8,12). V 1 , V 2 , and R consist of 10,000 normally distributed random numbers, N (1, 2), and R ∼ N (20, 1); V 2 represented the velocity of the pedestrian in this case.…”
Section: Simulation Results Analysis Of Four Modesmentioning
confidence: 99%
“…In rightturning collision-related research, Sitao et al put forward an intersection optimization design to reduce the collision probability between right-turning vehicles and pedestrians [11], but it cannot cover all possible right-turning collisions in intersections. Zhao et al have conducted research in intelligent vehicles active collision avoidance related fields [12]. Choi and Zhao et al adopted the autonomous emergency braking (AEB) system to avoid collisions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, their implementation is a major challenge for both rule-based control and data-driven decision-making. Readers are encouraged to refer to 31,32 for the appropriate analysis of key technologies for assistance systems for collision prevention. Multiple business giants in different countries are currently working on the production of AVs.…”
Section: Overview Of Mvccamentioning
confidence: 99%
“…Some articles review specific behaviours, such as car-following behaviour (Saifuzzaman & Zheng, 2014), lane changing behaviour (Koesdwiady et al, 2016), and intersection behaviour (Shirazi & Morris, 2016), while others review specific driver traits such as impulsiveness (Bıçaksız & Özkan, 2016), sensation seeking (Zhang et al, 2019), and aggressive driving behaviour (Alkinani, Khan & Arshad, 2020). Few articles review the use of machine learning-based technology in ITS Nguyen et al (2018), Martinez et al (2017), Alsrehin, Klaib & Magableh (2019) and Pamuła (2016), the evolution of vehicles' sensing technology and their effect on safety (Massaro et al, 2016), and collision avoidance in assistance systems for intelligent vehicles Dahl et al (2018), Zhao et al (2017) and Mukhtar, Xia & Tang (2015). The effect of policies on driver behaviour and safety has been reviewed in Shinar & Gurion (2019).…”
Section: Survey Analysismentioning
confidence: 99%